2012
DOI: 10.1021/jp209927m
|View full text |Cite
|
Sign up to set email alerts
|

Production of Nitrogen-Doped Graphene by Low-Energy Nitrogen Implantation

Abstract: Nitrogen doping of graphene is a suitable route to tune the electronic structure of graphene, leading to n-type conductive materials. Herein, we report a simple way to insert nitrogen atoms into graphene by low-energy nitrogen bombardment, forming nitrogen-doped graphene. The formation of nitrogen-doped graphene is investigated with high resolution X-ray photoelectron spectroscopy, allowing to determine the doping level and to identify two different carbon−nitrogen species. By application of different ion impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 29 publications
7
100
3
Order By: Relevance
“…In fact, the magnetic field induced electron 11 confinement in the ECR configuration generates high temperature electron distribution tails of nearly 30 eV which lead to a relatively high degree of N2 dissociation without a significant increase in the potential or ion bombardment energies. 53 Considering that for both set of samples, the treatment time was kept the same; the ECR process produced significantly higher pyridinic nitrogen as compared to the rf-PECVD process and as such corroborates the results presented by Zhao et al 51 Using molecular dynamics, Åhlgren et al have…”
Section: 39supporting
confidence: 82%
“…In fact, the magnetic field induced electron 11 confinement in the ECR configuration generates high temperature electron distribution tails of nearly 30 eV which lead to a relatively high degree of N2 dissociation without a significant increase in the potential or ion bombardment energies. 53 Considering that for both set of samples, the treatment time was kept the same; the ECR process produced significantly higher pyridinic nitrogen as compared to the rf-PECVD process and as such corroborates the results presented by Zhao et al 51 Using molecular dynamics, Åhlgren et al have…”
Section: 39supporting
confidence: 82%
“…Doping by keV ion implantation has been studied theoretically [14] and it was shown that the substrate enhances the chances for successfull indirect implantation. Experimentally, ion implantation in epitaxial graphene grown on SiC as well as on Ni(111) has been performed by irradiation with slow (keV) nitrogen ions at high fluences [15,16]. In freestanding graphene single atom substitution has been demonstrated [17].…”
Section: Cimap (Cea-cnrs-ensicaen-ucbn) 14070 Caen Cedex 5 Francementioning
confidence: 99%
“…The atoms would stem from the underlying substrate. It has already been proposed in a theoretical paper by Zhao et al that indirect implantation of graphene might be possible with keV ions [16]. In the case of SHI the ejection of surface material is caused by a different process, e.g.…”
Section: (B)mentioning
confidence: 99%
“…Note that, as a surface modifi cation approach, which species indeed plays the most important role in improving the electrochemical performance of an electrode material, it is still unclear now, although some work about the nitrogen-doped carbon coated electrode materials has already been reported for LIBs. [ 32 ] Here, N-doped carbon coating are initially adopted in Na 3 V 2 (PO 4 ) 3 cathode material for SIBs, and found, compared with the bare carbon coated Na 3 V 2 (PO 4 ) 3 , N-doped carbon coated Na 3 V 2 (PO 4 ) 3 composite exhibits a remarkable improvement in Na storage property, especially its rate performance. Furthermore, the modifi cation effects of various nitrogen types on electrochemical performance are explored in detail, and gives a direct evidence of what kind of N-doped species has the largest impact on an electrode material for SIBs.…”
Section: Introductionmentioning
confidence: 99%